The Strategy for Implementing Learning Program Evaluation in Improving the Quality of Student Learning at Nurul Fadhilah Islamic Boarding School - Tamimi Mujahid; Adila Aisyahrani; Inom Nasution; Ayu Putri Julia; Siti Syevila; Nurul Anjani Daulay; Hafiz Yusuf (Education Achievement: Journal of Science and Research, 2024)
Learning media is one of the important components in learning activities. Learning media should be a part that must be obtained. The teacher's attention is focused on each learning activity. Therefore, teachers need to learn how to organize media. Learn to be effective and learn how to teach while achieving learning objectives. The research method used in this study is to use qualitative research methods by directly observing and interviewing the leadership. The place of this research is in Nurul Fadhilah Islamic Boarding School. To support learning success, evaluation should continue to be carried out and learning media are available. Because, with the availability of educational media, students may think more concretely and this means that they can reduce verbalism in students.